À quoi s’intéressent les enseignants dans les exemples en formation ? Étude de l’utilisation par des stagiaires de ressources basées sur la vidéo - Simon Flandin; Marine Auby; Luc Ria (Recherches en Éducation)
This article reports on a case study on teachers’ video-enhanced education. Considering the fact that video exemplification is a thriving practice in the field although there is little consensus in the literature regarding its instructional issues, it seems appropriate to focus on the activity carried out by teachers in video-enhanced devices in order to identify promising characteristics (nature of the examples, types of associations between them, documentation methods, organization and scenarization, etc.). This study involved six trainees who used, during two sessions of 45 minutes, a digital device based on a « pedagogy of typical professional paths » (Durand, 2014; Ria & Leblanc, 2011). The goal was to better understand their use of video exemplification and sense-making. The results indicate that student teachers (i) preferentially target resources about "economic rules"; (ii) plebiscite classroom situations, always consulted; (iii) are particularly interested (even if they are sometimes disappointed) in the experts’ testimonies; (iv) initially show a distrust toward resources assumed to be theoretical; (v) get gradually interested in these resources during the second session. We conclude with several empirical and technological prospects for the design of video-enhanced devices for teacher induction.